Building Value Through Governance, Responsibility, and Sustainability - Permata Dewi, Ines; Zulfiati, Lies (Santoso Academy Network, 2026)
This study aims to examine whether the Independent Board of Commissioners, Board of Directors, CSR, and environmental performance influence company value. This study uses a quantitative research method with an associative approach. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2024 period. The sample was selected using a purposive sampling method and comprised 31 companies, yielding 124 observations. The results of this study show that the Independent Board of Commissioners has a negative influence on company value, as indicated by a negative coefficient. The Board of Directors' influence on company value is accepted. The influence of CSR on company value is accepted. The higher the intensity and quality of a company's CSR activities, the greater the value reflected in investors' and other stakeholders' perceptions. The influence of environmental performance on company value is accepted. The managerial implications of this study indicate that companies need to strengthen substantive implementation of GCG, not just formal compliance.